Public Procurement: Borders, Tensions and Interrelation with Private Law in the New Contractual Scenario - Cassagne, Juan Carlos (2015)
The establishment of the limits between the public law and the private law has been a hard to clarify. For that reason, the author brings a perspective about this division, focusing on the case of public procurement. Thus, in the first part he will explain the division between public law and private law, and how this division has evolved. Then, he will explain the consequences of the disruption of unitary theory on public procurement. Finally, he will show the inequality of the parts, the public prerogatives and the compensatory guarantees, all involved in the peculiarities of management contract, that distinguishes it from an private contract.